1978
DOI: 10.1128/aem.36.3.473-479.1978
|View full text |Cite
|
Sign up to set email alerts
|

Thermal resistance of naturally occurring airborne bacterial spores

Abstract: Simulation of a heat process used in the terminal dry-heat decontamination of the Viking spacecraft is reported. Naturally occurring airborne bacterial spores were collected on Teflon ribbons in selected spacecraft assembly areas and subsequently subjected to dry heat. Thermal inactivation experiments were conducted at 105, 111.7, 120, 125, 130, and 135 degrees C with a moisture level of 1.2 mg of water per liter. Heat survivors were recovered at temperatures of 135 degrees C when a 30-h heating cycle was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…While it has been observed that bacteria sometimes enter the clean room with humans (Puleo et al, 1978;Castro et al, 2004), other bacteria may be well adapted to the oligotrophic conditions of these environments as well as the chemicals used for cleaning the facility (La Duc et al, 2004). Furthermore, differences observed in microbial diversity and abundance between the three sampling dates suggest that these populations are not stable and may fluctuate significantly throughout the spacecraft assembly process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been observed that bacteria sometimes enter the clean room with humans (Puleo et al, 1978;Castro et al, 2004), other bacteria may be well adapted to the oligotrophic conditions of these environments as well as the chemicals used for cleaning the facility (La Duc et al, 2004). Furthermore, differences observed in microbial diversity and abundance between the three sampling dates suggest that these populations are not stable and may fluctuate significantly throughout the spacecraft assembly process.…”
Section: Discussionmentioning
confidence: 99%
“…These controlled conditions, coupled with periodic cleaning with chemical detergents (NASA-KSC, 1999), result in a harsh, nutrient-limited environment that is not conducive to microbial growth (La Duc et al, 2007a). However, although the stringent conditions within these facilities are effective in reducing the overall microbial load (Venkateswaran et al, 2001;La Duc et al, 2007a), they may also select for ''hardy'' microorganisms capable of tolerating prolonged periods of desiccation, extremes of temperature, and exposure to UV light or hydrogen peroxide (Puleo et al, 1978;La Duc et al, 2003, 2007aKempf et al, 2005;Newcombe et al, 2005;). A number of microbes have been isolated that can tolerate multiple environmental stresses and have been reported to survive under simulated and actual space conditions (Newcombe et al, 2005;Osman et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Many oligotrophic microorganisms are capable of colonizing inorganic surfaces like metal (Nagarkar et al , 2001) or glass and the presence of such microorganisms may lead to many problems for space missions, including biocontamination, biofouling, and biodeterioration (Wainwright et al , 1993). Strains isolated from these environments have also been shown to tolerate decontamination strategies, such as UV and gamma radiation treatment (Puleo et al , 1978; La Duc et al , 2003, 2007; Newcombe et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Viking 1 and 2 spacecraft were launched in August and September 1975, respectively, to explore the planet Mars and specifically look for signs of extant extraterrestrial life ( 1 ). As part of a routine environmental microbial monitoring of the Vehicle Assembly Building (VAB) and the Manned Spacecraft Operations Building (MSOB) facilities in Cape Canaveral, FL, 32 Teflon ribbons were left out for 7 days and used to collect airborne microorganisms ( 2 ). The Teflon ribbons were then exposed to a total of 6 different heat treatments at three different time cycles ( 2 ).…”
Section: Genome Announcementmentioning
confidence: 99%